Pengaruh Karakteristik Wirausaha Dan Modal Usaha Terhadap Perkembangan Gerai UMKM Di Desa Purwodadi Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Lela Suryani; Titin Agustin Nengsih; Nurlia Fusfita (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aims of this study were (1) to determine the influence of entrepreneurial characteristics and venture capital simultaneously on the development of MSME outlets in Purwodadi Village, Tebing Tinggi District, West Tanjung Jabung Regency. (2) To determine the effect of entrepreneurial characteristics and business capital partially on the development of MSME outlets in Purwodadi Village, Tebing Tinggi District, West Tanjung Jabung Regency. This research uses a quantitative descriptive approach. This study explains whether there is an influence of entrepreneurial characteristics and business capital on the development of MSME outlets in Purwodadi Village, Tebing Tinggi District, Tanjung Jabung Barat Regency. The population in this study were all SMEs, totaling 23 SMEs, the researchers used a saturated sampling method. And using the data analysis method Research Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination. Based on the results of the F test (simultaneous test) it can be concluded that the entrepreneurial characteristics and venture capital together have a significant effect on the development of MSME outlets in Purwodadi village because the significant value is 0.000 <0.05 and the fcount value is 15.026 > ftable is 3.466, so this means that the entrepreneurial characteristics and venture capital variables simultaneously influence the development of MSME outlets in Purwodadi Village, Cliff High District, West Tanjung Jabung Regency. And based on the results of the T test (partial test) for the two variables of entrepreneurial characteristics and business capital on the development of MSME outlets in Purwodadi village, it can be concluded that the entrepreneurial characteristics and venture capital variables have a positive and significant effect on the development of MSME outlets in Purwodadi Village, High Cliff District, Tanjung Regency. west jab.